Concomitant BCR-ABL1 positive chronic myelogenous leukemia emerging in a patient with MPL W515L associated primary myelofibrosis - Juan C. Gomez-Gelvez, MD; Elena Ivan, MD; Bryan L. Betz, PhD; Megan S. Lim, MD, PhD (Elsevier, 2016)
Myeloproliferative neoplasms (MPNs) are clonal hematopoietic stem cell disorders characterized by proliferation of one or more cell lineages in the bone marrow. At present, the main criterion in the 2008 World Health Organization classification of MPNs is the presence of an underlying genetic abnormality. These mutations are generally mutually exclusive except for rare reports in the literature. We report for the first time a detailed analysis of the clinical, histologic and cytogenetic/molecular features of a patient who initially presented with MPL W515L positive primary myelofibrosis and over the course of five years developed an MPN associated with both BCR-ABL1 and MPL W515L mutation. We discuss the diagnostic challenges and therapeutic implications of concomitant BCR-ABL1 translocation with MPL W515L mutation. Multiple genetic alterations may simultaneously coexist in patients exhibiting features of myeloproliferative disorders.